Perkembangan Emosi Pada Remaja Muslim Pasca-Perceraian Orang Tua - Dewi Apriliani; Asysyfa Putri Humairah; Muhammad Zikri Akbar; Siti Sri Yarni; Mahdia Fadhila (Faculty of Ushuluddin and Humanities, 2024)
The emotional development of Muslim youth after the divorce of their parents. Parents' divorce can have a major impact on young Muslims, including complex emotional changes. Social support from family, peers and the religious community plays an important role in their emotional development. This allows Muslim youth to share the problems they are facing, strengthens their sense of belonging and makes them feel supported in the process of emotional healing. This study uses a literature study method that collects data from various journals, articles, and theses related to the emotional development of Muslim adolescents after their parents' divorce. The results of the study show that post-divorce Muslim adolescents experience complex emotional changes. They need social support and a deeper understanding of Islamic teachings to help them overcome the emotional challenges they face. This research is expected to provide insight into the emotional development of Muslim youth after experiencing parental divorce and the factors that influence it. Keywords: Emotional Development; Muslim Teenagers; Parents Divorce.